Análisis de la viabilidad técnico-financiera de la perforación con tubería flexible híbridos en el Campo Caño Sur (2019)
The project analyzed the technical and financial viability of the use of hybrid drilling rigs with flexible pipe in the Caño Sur Field in Meta, for this, several selection matrices were made where we compared conventional drills used in the field, pipe drill Flexible and flexible tubing drills. In this way it was possible to determine among all these which was the most suitable drill for a drilling campaign by grouping everything in a main matrix. The historical data of shallow drilling at five thousand feet of conventional drills and hybrids in different locations were compared in order to show with facts the results of the applicability of the HCTD technology.